2013
DOI: 10.1371/journal.pone.0058871
|View full text |Cite
|
Sign up to set email alerts
|

Steviol Reduces MDCK Cyst Formation and Growth by Inhibiting CFTR Channel Activity and Promoting Proteasome-Mediated CFTR Degradation

Abstract: Cyst enlargement in polycystic kidney disease (PKD) involves cAMP-activated proliferation of cyst-lining epithelial cells and transepithelial fluid secretion into the cyst lumen via cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel. This study aimed to investigate an inhibitory effect and detailed mechanisms of steviol and its derivatives on cyst growth using a cyst model in Madin-Darby canine kidney (MDCK) cells. Among 4 steviol-related compounds tested, steviol was found to be the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…reported a strong expression of CFTR in cyst-lining cells from ADPKD patients and shown that fluid accumulation within cysts involves CFTR-like Cl − currents ( Hanaoka et al, 1996 ). Further evidence comes from the cyst inflation being slowed down either through pharmacological inhibition of CFTR or by reducing its apical expression in cyst-lining cells ( Blazer-Yost et al, 2010 ; Li et al, 2004 , 2012 ; Yang et al, 2008 ; Yuajit et al, 2013 , 2014 ). Also, a milder renal disease was observed in few patients affected simultaneously by ADPKD and CF ( Xu et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…reported a strong expression of CFTR in cyst-lining cells from ADPKD patients and shown that fluid accumulation within cysts involves CFTR-like Cl − currents ( Hanaoka et al, 1996 ). Further evidence comes from the cyst inflation being slowed down either through pharmacological inhibition of CFTR or by reducing its apical expression in cyst-lining cells ( Blazer-Yost et al, 2010 ; Li et al, 2004 , 2012 ; Yang et al, 2008 ; Yuajit et al, 2013 , 2014 ). Also, a milder renal disease was observed in few patients affected simultaneously by ADPKD and CF ( Xu et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the MDCK cells were shown to be capable of transcellular water flow. Several works have since shown that cAMP stimulation by forskolin activates apical chloride channels and induces transepithelial water flow into the MDCK lumen (Buchholz et al 2014a;Li et al 2004;Tanner et al 1992;Yuajit et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Madin-Darby canine kidney (MDCK) cells form cysts when cultured in a collagen I or matrigel matrix. These cells have served as a kidney cell model for the analysis of the regulation of lumen formation and enlargement in response to chloride and water secretion in the presence of forskolin, which leads to elevation of cAMP (Buchholz et al 2014a;Li et al 2004;Tanner et al 1992;Yang et al 2008;Yuajit et al 2013). In all of these experiments, the authors have used MDCK cells expressing endogeneous or transfected CFTR, and cyst enlargement occurred over culture periods of 6 to 12 days, during which time it can be reasonably assumed that cell proliferation and cell rearrangement both contributed significantly to the observed structural changes of the cyst and lumen.…”
Section: Introductionmentioning
confidence: 99%
“…stevioside, rebaudiosides A and C and ducloside A of Stevia rebaudiana have the growth inhibitory activity or anticancer effects. The antitumor activity has been observed in studies conducted in Human laryngeal epithiloma cells (HEp2), the MTT assay (measured the cell viability) for treated cells by acetone extract of Stevia rebaudiana showed that 1:8 dilution of the acetone extract (the effective drug concentration) had anticancer and anti-proliferative activities against abnormal cells [79]. Some researchers suggested that polyphenol, antioxidant and antiinflammatory effects of Stevia.…”
Section: Anti-cancermentioning
confidence: 99%
“…Deshmukh and Kedari (2014) founded the methanol and ethanol extracts of stevioside can be used to anticancer activity against Caco-2andCaski cell lines as compared to water extracts [78]. Yuajit et al (2013) revealed steviol inhibiting Madin-Darby canine kidney (MDCK) cyst growth by reducing cystic fibrosis trans membrane conductance regulator (CFTR) expression levels that this inhibition related to used dose of Stevia and expressed dose up to 200 microM had no effect on MDCK cell. stevioside, rebaudiosides A and C and ducloside A of Stevia rebaudiana have the growth inhibitory activity or anticancer effects.…”
Section: Anti-cancermentioning
confidence: 99%